Analisis Kecenderungan Sedimentasi Waduk Bili-Bili Dalam Upaya Keberlanjutan Usia Guna Waduk - Achsan, Achsan; Bisri, Mohammad; Suhartanto, Ery (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
Bili-Bili Reservoiris one of the large streservoirsin Province of South Sulawesi whichis regulated by BBWS Pompengan Jeneberang. Bili-Bili reservoirs was planne deffective for 50 years, recently in 2011(the reference of latest data) thi sreservoir has been in operation for13 years since was built. In 2004 there were land slides from the Mount Bawakaraeng in up stream reservoir sand causing high rates of sedimentation in the reservoir. This study was conducted to determine the percentage of sediment that settles in the reservoir storage capacity, the effectiveness of Reservoir remaining and also the efforts made to maintaining the effectiveness sof reservoirs. In this study, the distribution sediments calculations based on the actual measurement and the enlargement Empirical Area Increment Methodand Empirical Area Reduction Method. The effectiveness of use full life of BiliBili to the reservoiris calculated using volume approach hand elevation approach. Trend Sedimentation tendencywhich was entering in 2011 was about 84.81millionm 3 of total sediments with apercentage of 79.17% was in the effective storage area, 18.14% in the area of dead storageend 2.69% in the flood control pool..Based on the analysis of the effectiveness life of Bili-Bili by reservoir elevation approach of +59.00, the Bili-Bili reservoir has no longer the effectiveness, but by using the yield residualolume approachin reservoir has still effectiveness of 11.5 years.Keywords: Bili-Bili Reservoir, Sedimentation, StorageCapacity, Reservoir usefull life